67.1k views
4 votes
When she subtracts 4 from both sides

is
Kanssa begins to solve the equation
*(x-14) + 11 ==x-(x-4). Her work is correct and is
What is the value of x?
shown below
O-1
{ cx29)+11 = {x=(x-4)
{x-7+11 = {x-x+4
2x+4= -3x +4
ooo
Now

User Jon Kyte
by
4.2k points

1 Answer

3 votes

Answer:

If your equation is (x - 14) + 11 = x - (x - 4), then x = 7

Explanation:

Your equation is (x-14) + 11 ==x-(x-4).

If we simplify:

x - 14 + 11 = x - x + 4

x - 3 = 4

x = 4 + 3

x = 7

or...

You say

x - 7 + 11 = 2x - x + 4 ?

User Khadka Pushpendra
by
6.1k points